Teori Pendidikan Agama Kristen Berbasis Relasi: Membangun Komunitas Saling Mengasihi di Lingkungan Sekolah - Baginda Sitompul; Meilan Pakpahan; Lesti Simanjuntak; Noviyanti Herlina; Ardina Gajah (Journal of Mandalika Literature, 2025)
This article discusses the theory of relationship-based Christian religious education: building a community of mutual love in the school environment. This research uses literature research or library study methods. With this method the author can analyze literature sources that are relevant and related to the objectives of this research and express them in a research result. Christian religious education is a conscious effort that is planned to instill the basic teachings of Jesus Christ and the development of faith by creating learning situations and learning systems so that students are able to develop potential or spiritual, noble morals, skills needed by students and the surrounding community. Relationship-based Christian religious education aims to build a community of mutual love in schools through positive relationships between teachers and students and between students. This approach emphasizes the application of Christian values ​​such as love, forgiveness, and respect. This research examines how Christian religious education can create an inclusive environment that supports student character development. The research method used is literature study, with data sources from books, scientific journals and relevant articles. Relationship-based Christian religious education is effective in creating a community that is full of love, respects differences, and supports each other, as well as encouraging students' spiritual and social development in an inclusive and tolerant environment. Implementing these values ​​in schools can strengthen relationships between students, foster a sense of togetherness, and create space for each individual to develop. Teachers should also be role models in implementing the values ​​of love, forgiveness and mutual respect, as well as creating an environment that is inclusive and supportive of every individual regardless of their background. This concept contributes to the formation of better student character.